2020
DOI: 10.1155/2020/6726798
|View full text |Cite|
|
Sign up to set email alerts
|

Patient Delay in Initiating Tuberculosis Treatment and Associated Factors in Oromia Special Zone, Amhara Region

Abstract: Background. Tuberculosis (TB) is a major global public health problem. The disease is a leading cause of morbidity and mortality in Ethiopia. Early identification of cases and commencement of effective chemotherapy is an effective method to control the spread of tuberculosis. Delay in diagnosis and starting tuberculosis treatment increases severity, risk of mortality, and transmission of the disease in the community. Objective. The purpose of this study is to assess the magnitude of patient delay in initiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…According to the finding of this review, patients with extra pulmonary TB patients had a higher risk of treatment seeking delay than its counterparts which agrees with other similar study [14]. Similarly, another study also found that extra pulmonary Tuberculosis is significantly associated with delay [36,40].…”
Section: Plos Onesupporting
confidence: 90%
See 3 more Smart Citations
“…According to the finding of this review, patients with extra pulmonary TB patients had a higher risk of treatment seeking delay than its counterparts which agrees with other similar study [14]. Similarly, another study also found that extra pulmonary Tuberculosis is significantly associated with delay [36,40].…”
Section: Plos Onesupporting
confidence: 90%
“…A patient who travelled farther than 10 kilometers from health facilities, have a higher delay as compared to those who travelled less than 10 kilometers. The result of this study is in line with other studies conducted in Oromia Special Zone and North Wollo [14,18]. This might be due to rural residency makes it difficult to travel to health facility due to…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…Variables with a p-value < 0.05 in the multivariable analysis were considered as having a statistically significant association with the outcome (diagnosis or treatment delay). Additional models were created for sensitivity analyses to evaluate a 14 day delay used by some studies [13,22], compared a 21 day diagnosis delay used by others [23][24][25][26][27]. An analysis was also conducted using the median (> 1 day) to define treatment delay.…”
Section: Discussionmentioning
confidence: 99%